Decision Tool for Predicting Outcomes in Geriatric Acute Mesenteric Ischemia. Issue 8 (August 2018) - Murphy, Kyle C.; Kay, Danielle; Davenport, Daniel L.; Bernard, Andrew
Acute mesenteric ischemia is a morbid disease process that is most common in elderly patients who often have multiple medical comorbidities. Intervention can progress to costly and futile care. The goal of this study was to develop a tool for practitioners to assess the risk of mortality. Patients treated at our institution over the past decade diagnosed with acute mesenteric ischemia were identified. Patients aged less than 65 years were excluded. Data were collected by retrospective chart review. Univariate analysis was used to identify significant risk factors for death. Decision tree analysis yielded a prognostic tool to assess death risk. Univariate analysis demonstrated that lactate (P ≤ 0.001) and pressor requirement (P ≤ 0.001) were predictive of death. Decision tree analysis showed that 79 per cent of patients with day of surgery (DOS) lactate ≥5.4 died postoperatively. Seventy per cent of patients with DOS lactate <5.4 progressed to death if they required pressors and had a creatinine >1.18. Only 6.1 per cent patients with a DOS lactate <5.4, creatinine <1.54, and no pressor requirement progressed to death. Several variables can be used to set expectations for families and help guide decision-making. Our tool was predictive of outcomes in 82 per cent of our study population.